1996
DOI: 10.2134/jeq1996.00472425002500060036x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Effectiveness and Stability of Aqueous Lead Immobilization by Hydroxyapatite

Abstract: The effects of Ca, K, Na, calcite, and EDT A on Pb immobilization by hydroxyapatite [CaIO(P04)6(OHh; HAl were investigated. The stability of hydroxy pyromorphite [PbIO(P04MOHh; HPJ (a reaction product of HA with Pb) and the effectiveness of using HA to immobilize Pb in Pb-contaminated soils also were examined. Neither Na nor K affected Pb immobilization. Aqueous Ca and calcite slightly inhibited Pb immobilization, but HA still reduced aqueous Pb > 97% in the presence of these species; however, EDTA significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 18 publications
0
34
1
2
Order By: Relevance
“…Another method to immobilize lead is application of organic fertilizers or phosphates. In particular, solution lead concentration in Pb-enriched soil can be substantially reduced by adding hydroxyapatite [Ca 5 (PO 4 ) 3 (OH)] (Ma et al, 1992;Ma, 1996), monocalcium phosphate [Ca(H 2 PO 4 ) 2 Á2H 2 O] (Kalbasi et al, 1995), or Na 2 HPO 4 (Rabinovitz, 1993). This response is attributed to the precipitation of hydroxypyromorphite [Pb 10 (PO 4 ) 6 (OH) 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another method to immobilize lead is application of organic fertilizers or phosphates. In particular, solution lead concentration in Pb-enriched soil can be substantially reduced by adding hydroxyapatite [Ca 5 (PO 4 ) 3 (OH)] (Ma et al, 1992;Ma, 1996), monocalcium phosphate [Ca(H 2 PO 4 ) 2 Á2H 2 O] (Kalbasi et al, 1995), or Na 2 HPO 4 (Rabinovitz, 1993). This response is attributed to the precipitation of hydroxypyromorphite [Pb 10 (PO 4 ) 6 (OH) 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ainda segundo Cotter-Howells e Caporn (1996) e Ma (1996), o uso de fosfatos em solos contaminados com Pb pode reduzir a biodisponibilidade desse elemento, graças à formação de fosfato de Pb (por exemplo, piromorfita).…”
Section: Solounclassified
“…The formation of pyromorphite is a step-wise process which involves the dissolution of the Pb and P minerals and the precipitation of pyromorphite, hence the dissolution of either Pb or P minerals will determine the rate of pyromorphite formation in the soil (Arnich et al, 2003;Ma, 1996;Yang et al, 2001). In most cases, however, soil P availability is greater than Pb (Lindsay, 2001) and pyromorphite formation is limited by the dissolution of Pb 2+ into soil solution.…”
Section: Formation and Stability Of Lead-phosphate (Pyromorphite) In mentioning
confidence: 99%
“…On the other hand, a laboratory study using hydroxy-pyromorphite and anion resins to remove P from solution simulating P-uptake by plants indicated that pyromorphite was still stable in a P depleted environment (Ma, 1996). It is very clear that, however, the role of plants in mineral dissolution is beyond a simple P uptake.…”
Section: Mycorrhizal Fungi In Rhizosphere and Their Role In Mineral Dmentioning
confidence: 99%
See 1 more Smart Citation